(untitled) (Ágora Journal, 2021)
This paper focuses on the interim governments of the Portuguese empire between 17th and 18th century. Interim governments were those formed caused by the absence of owner governor appointed by the Portuguese Crown. This research analyzes questions regarding the formation of provisional governments, including the reasons that led to the vacancy of the post, who were the people who assumed the governmental responsibilities, how the legislation of the Portuguese empire predicted the formation of the interim office. The objective is to understand the existence of interim governments within a larger political framework which regarded these temporary authorities as a strategy and not simply as emergency substitutes in circumstances of unexpected vacancies.